The effects of monochromatic LED light from one to 14 days of age on the growth, muscle development, and blood parameters of goslings - JJ Xue; XF Huang; ZL Liu; Y Chen; H Zhong; Y Luo; QG Wang; C Wang (South African Journal of Animal Science)
This study was conducted to investigate the effects of monochromatic light on the growth performance, muscle development, and blood parameters of goslings from one to 14 days of age. A total of 192 male Sichuan White goslings were randomly assigned at hatching to four treatment groups of 48 birds, with six replications per group. These treatment groups were exposed to white light, red light, green light, or blue light in four environmentally controlled chambers. At 14 days of age, body weight and feed intake were determined on a per-pen basis, and one gosling per pen was selected for the collection of blood and muscle samples. All data were subjected to an analysis of variance. The results showed that the blue and green light groups had lower average daily feed intake and feed/gain ratios than the red and white light groups, but no differences in average daily gain and final body weight were found. Moreover, the leg muscle weight and leg muscle fibre diameter and density were unaffected by exposure to monochromatic light. Similarly, the goslings from the four treatment groups exhibited comparable plasma levels of growth hormone, insulin-like growth factor 1, immunoglobulin Y, and immunoglobulin M. Our study indicates that short-term exposure to different light colours does not affect the growth of goslings, but light with short wavelengths decreases feed intake and improves feed conversion efficiency.